Participação da quimiocina CCL3 na carcinogênese bucal induzida por 4-nitroquinolina-1-óxido em camundongos - Janine Mayra da Silva (2012)
The chemokine CCL3 displays a diversity of roles that may contribute to worse prognosis in oral carcinogenesis. The aim of this study was to evaluate the role of CCL3 in 4-nitroquinoline-1-oxide (4NQO)-induced oral carcinogenesis. C57BL/6 (wild type - WT) and CCL3 deficient (CCL3-/-) male mice were treated with 4NQO in drinking water at concentration of 50 ìg/ml during 20 or 28 weeks Their tongues were collected for macroscopic, histopathological and immunohistochemical analysis. Also, the cytokine levels in tongue lesions were evaluated by ELISA. Our results showed a significantly higher incidence of tumors in tongue of WT- in comparison with CCL3-/-- treated mice. Consistently, microscopic analysis demonstrated a pronounced cytological atypia in the WT-treated group. The immunoexpression of PCNA and Ki67 revealed a significant increase of the proliferative index in WT compared with CCL3-/--treated group. The concentration of CCL3, TNF-á, CCL5 and CCL11 was significantly enhanced after 4NQO treatment, but CCL3-/--treated mice showed lower TNF-á level when compared with WT. In conclusion, these data suggest a protective effect of CCL3deletion in oral tongue carcinogenesis which may be associated with local changes in TNF-á production.